Feed the Future Malawi Improved Seed Systems and Technologies (MISST) Project: Orange-fleshed Sweetpotato Component - International Potato Center (2017)
At the end of its third year, the project enabled over 48,000 households to produce and consume pro-vitamin A rich orange-fleshed sweetpotato (OFSP) varieties. We have built the capacity of private sector, government and NGO’s to scale out OFSP technologies for the betterment of smallholder farmers in Malawi.